2009
DOI: 10.1007/s10488-009-0222-2
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Practice-Based Research Networks as a Platform for Mental Health Services Research

Abstract: Practice-based research networks (PBRNs)—collaborations of practice settings that work together to generate research knowledge—are underused in mental health services research. This article proposes an agenda for mental health services research that uses a variety of PBRN structures and that focuses on what really happens in practice, the effectiveness of practice innovations in real world care, the challenges of implementing evidence supported interventions, modification of clinician behavior, and assessment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 62 publications
2
37
0
Order By: Relevance
“…Additional lessons can be derived from research programs in the field of mental health that have not been represented in this series, such as the process and outcome studies by Jacqueline Persons (e.g., Persons, Roberts, Zalecki, & Brechwald, 2006) and David Burns (e.g., Burns & Nolen-Hoeksema, 1992) in specialized cognitive therapy centers, as well the work that has been conducted within the Healthy Families America Research Practice Network (Galano & Schellenbach, 2007) on the prevention of child maltreatment (see Castonguay et al, 2013;McMillen, Lenze, Hawley, & Osbourne, 2009). Moreover, much can be learned from partnerships of practitioners and researchers in a wide range of health care and medical fields, including nursing, primary care, pediatrics, and family medicine.…”
Section: Resultsmentioning
confidence: 99%
“…Additional lessons can be derived from research programs in the field of mental health that have not been represented in this series, such as the process and outcome studies by Jacqueline Persons (e.g., Persons, Roberts, Zalecki, & Brechwald, 2006) and David Burns (e.g., Burns & Nolen-Hoeksema, 1992) in specialized cognitive therapy centers, as well the work that has been conducted within the Healthy Families America Research Practice Network (Galano & Schellenbach, 2007) on the prevention of child maltreatment (see Castonguay et al, 2013;McMillen, Lenze, Hawley, & Osbourne, 2009). Moreover, much can be learned from partnerships of practitioners and researchers in a wide range of health care and medical fields, including nursing, primary care, pediatrics, and family medicine.…”
Section: Resultsmentioning
confidence: 99%
“…The knowledge development function of practitioner-based research can take the shape of large-scale, multi-agency joint ventures or it can be as simple as pilot testing an ESI in a particular organization and documenting the lessons learned in the "living" process of implementation (Martinez-Brawley, 1995). McMillen et al (2009) identified four characteristics of practice-based research. First, it produces data that reflect the conditions of providing services in community-based programs, not academic settings.…”
Section: Practice-based Researchmentioning
confidence: 99%
“…McMillen et al (2009) suggested that practice-based research be used to investigate how organizational issues like funding, regulation, and accreditation affect clinical decision making. They maintain that a bottom-up process of inquiry is better suited to complexity of that topic than a traditional research design would be.…”
Section: Teaching the Ebp Process In Social Work Educationmentioning
confidence: 99%
See 2 more Smart Citations